WAYS TO ORGANIZE EFFECTIVE PACKAGING AND DELIVERY SYSTEMS IN ELECTRONIC COMMERCE (Marketing Journal, 2025)
This article examines the challenges of environmental sustainability in e - commerce and strategies to address them. In particular, it analyzes the environmental impact of packaging materials and delivery systems and the possibilities for their transformatio n into environmentally friendly methods. The use of biodegradable materials, reducing carbon footprints, and innovative logistics approaches are discussed. The results of this study are aimed at providing useful recommendations for e-commerce companies to reduce environmental problems.
Keywords: environmental sustainability; packaging; delivery; carbon footprint; plastic; starch; minimalist packaging; innovative approach 158